2004
DOI: 10.1002/cne.20184
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal apoptosis, development, and sex difference in the lateral septum of rats

Abstract: To determine whether apoptosis is involved in the formation of the structure and morphological sex difference of the lateral septum (LS), the postnatal developmental changes in the number of apoptotic cells were examined in the LS on postnatal day 1 (PD1 = birth day), 4, 6, 8, 11, 16, and 31 in male and female rats. Apoptotic cells were immunohistochemically detected by antibody against single-stranded DNA (ssDNA) or active caspase-3. The volume of the LS was also measured and was found to increase with age. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…Sections were prepared as described previously (Hatta et al, 2002). Apoptotic cells were detected with polyclonal rabbit anti-singlestranded DNA (ssDNA) antibody (DAKO Japan, Kyoto, Japan) in the condylar cartilage at E18.5 (Nd = 4, Ne = 4) (Tsukahara et al, 2004).…”
Section: Immunohistochemistry For Cell Proliferation and Apoptosismentioning
confidence: 99%
“…Sections were prepared as described previously (Hatta et al, 2002). Apoptotic cells were detected with polyclonal rabbit anti-singlestranded DNA (ssDNA) antibody (DAKO Japan, Kyoto, Japan) in the condylar cartilage at E18.5 (Nd = 4, Ne = 4) (Tsukahara et al, 2004).…”
Section: Immunohistochemistry For Cell Proliferation and Apoptosismentioning
confidence: 99%
“…Recently, it has been suggested that the number of newly generated cells reaching the adult anterior accessory olfactory bulb is also sexually differentiated, with male rats exhibiting higher numbers of newborn cells (Peretto et al, 2001). In addition to neurogenesis and cell survival, it has been suggested that sex differences in cell numbers in several neural structures develop through sex-steroid-sensitive mechanisms that regulate apoptosis (Nordeen et al, 1987;Kirn & DeVoogd, 1989;Kirn & Schwabl, 1997;Stokes et al, 2004;Tsukahara et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, control of cell number by apoptotic cell death contributes to creating sex differences in cell number in several SDNs (Forger, 2009; Tsukahara, 2009). We found that the number of apoptotic cells in the male LSi is larger than that of the female LSi on PD16 (Tsukahara et al, 2004). The sex difference in the loss of cells by apoptosis during the late postnatal period is a contributing factor for producing the sex difference in neuron number of the LSi in adulthood.…”
Section: Lordosis-inhibiting System In the Lsmentioning
confidence: 90%
“…The LSi is one of the SDNs in the rat brain. The volume of the LSi in prepubertal female rats is larger than that of same-aged male rats, however, there are no sex differences in the volume of the LSd and LSv (Tsukahara et al, 2004). The number of LSi neurons in adult female rats is greater than that in adult male rats, while there are no sex differences in the number of neurons in the LSd and LSv (Segovia et al, 2009).…”
Section: Lordosis-inhibiting System In the Lsmentioning
confidence: 99%
See 1 more Smart Citation